Growth projections reveal local vulnerability of Mediterranean oaks with rising temperatures - Gea-Izquierdo, Guillermo; Fernández-de-Uña, Laura; Cañellas, Isabel (Forest Ecology and Management, 2013)
Growth projections using ecological models fitted to data collected along climatic gradients can help to understand how forests will respond to climate change. Stem growth of two Mediterranean oaks was predicted using nonlinear multiplicative models as a function of precipitation and minimum temperature of the hydrological year fitted to dendrochronological data. The growth of both species increased nonlinearly with accumulated precipitation before reaching an asymptote, but the species with a warmer niche (Q. ilex, an evergreen species) required lower levels of precipitation to achieve high relative growth. The species-specific relationship between growth and minimum temperature exhibited an optimum for the two species. Trees were negatively affected by high minimum temperatures whereas they responded negatively (Q. ilex) or neutrally (Q. pyrenaica, a deciduous species) to low temperatures along the climatic gradient analyzed. Growth would decrease rapidly when minimum temperatures rose above approximately 7 °C for Q. pyrenaica and 9 °C for Q. ilex. Most growth projections suggest a likely future decrease in productivity along the species range for Q. pyrenaica and particularly at species-specific warm, dry locations pointed to a future drastic reduction in productivity as a result of the increase in temperatures without a paired increase in precipitation forecasted by the different climate scenarios considered. In agreement with results from studies modeling future distribution of species this suggests that Q. pyrenaica could be threatened by climate change at the species local dry edge where, in addition, stands often present a lack of seed regeneration. More drought tolerant Q. ilex might profit from warming temperatures at cold northern locations but would also reduce productivity at warm, dry locations. Stem growth was successfully modeled using biologically meaningful species-specific responses to climate which provided key ecological information to understand the functional response of the two species. The models used have much potential to be applied with dendroecological data to study the response of forests to climate change.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Dendroecology; Forest decline; Global change; Nonlinear response; Quercus ilex; Quercus pyrenaica

Intensity and timing of warming and drought differentially affect growth patterns of co-occurring Mediterranean tree species - Granda, Elena; Julio Camarero, J; Gimeno, Teresa E; Martínez-Fernández, Jesús; Valladares, Fernando (EUROPEAN JOURNAL OF FOREST RESEARCH, 2013)
Climate change involves warmer temperatures, altered precipitation patterns, increased climatic variability and, in Mediterranean regions, increased frequency and severity of droughts. Tree species may show different growth responses to these components of climatic change, which may trigger changes in forest composition and dominance. We assessed the influence of recent climatic changes on secondary growth of mature trees from four species co-occurring in a Mediterranean continental forest: Quercus ilex, Quercus faginea, Pinus nigra and Juniperus thurifera. We used dendrochronology to relate radial-growth variables \{[\}earlywood and latewood widths, basal area increment (BAI)] to annual and seasonal climatic variables for the period 1977-2007. Our results showed that Q. faginea BAI has declined, whereas J. thurifera BAI has increased over time while Q. ilex and P. nigra have maintained their growth rates. Growth was mainly favored by higher precipitations and tree size for all species. Reduced growth during extremely dry years was observed for all study species, but all of them except Q. faginea recovered their growth levels 2 years after drought. Our findings illustrate how the effects of climatic changes on growth should include analyses of seasonal climatic trends and extreme events such as severe droughts. We conclude that the seasonal timing of warming and precipitation alterations leading to drought events caused contrasting effects on growth of co-occurring Mediterranean tree species, compromising their future coexistence.
Keywords: climate change; Coexistence; Dendroecology; Drought; Mediterranean forests; Radial growth

Increasing Drought Sensitivity and Decline of Atlas Cedar (Cedrus atlantica) in the Moroccan Middle Atlas Forests - Linares, Juan C; Taiqui, Lahcen; Julio Camarero, Jesus (FORESTS, 2011)
An understanding of the interactions between climate change and forest structure on tree growth are needed for decision making in forest conservation and management. In this paper, we investigated the relative contribution of tree features and stand structure on Atlas cedar (Cedrus atlantica) radial growth in forests that have experienced heavy grazing and logging in the past. Dendrochronological methods were applied to quantify patterns in basal-area increment and drought sensitivity of Atlas cedar in the Middle Atlas, northern Morocco. We estimated the tree-to-tree competition intensity and quantified the structure in Atlas cedar stands with contrasting tree density, age, and decline symptoms. The relative contribution of tree age and size and stand structure to Atlas cedar growth decline was estimated by variance partitioning using partial-redundancy analyses. Recurrent drought events and temperature increases have been identified from local climate records since the 1970s. We detected consistent growth declines and increased drought sensitivity in Atlas cedar across all sites since the early 1980s. Specifically, we determined that previous growth rates and tree age were the strongest tree features, while Quercus rotundifolia basal area was the strongest stand structure measure related to Atlas cedar decline. As a result, we suggest that Atlas cedar forests that have experienced severe drought in combination with grazing and logging may be in the process of shifting dominance toward more drought-tolerant species such as Q. rotundifolia.
Keywords: basal area increment; Cedrus atlantica; climate change; Dendroecology; Drought; Forest structure; partial redundancy analysis

Tree-rings reflect the impact of climate change on Quercus ilex L. along a temperature gradient in Spain over the last 100years - Gea-Izquierdo, G.; Cherubini, P.; Cañellas, I. (Forest Ecology and Management, 2011)
We analyzed tree rings over the past 100 years to understand the response of Quercus ilex L. to climate change at four different sites along a temperature gradient in a highly anthropogenically transformed ecosystem. To test the hypothesis of a climate change related decrease in productivity at warmer sites, we discuss the effect of historical management on the growth of forest stands and the spatio-temporal variability of growth in response to climate, analyzing departures from linearity in that relationship. We reconstructed stand history and investigated past growth trends using tree-rings. Then we used a dendroecological approach to study the regional, local and age-dependent response to climate, analyzing the relationship between precipitation and tree growth using non-linear mixed models. Tree rings reﬂected the origin of the studied landscape, mainly a simpliﬁcation of an original closed forest and progressive canopy opening for agrosilvopastoral purposes after the mid 1800s. As expected, trees were principally responding to water availability, and regional growth (as expressed by the ﬁrst principal component from the matrix of chronologies) was highly responsive to hydrological year precipitation (r = 0.7). In this water limited ecosystem, the response of growth to precipitation was asymptotic and independent of age, but variable in time. Maximum growth was variable at the different sites and the non-linear function of growth saturated (i.e. reached an asymptote) at temperature dependent site speciﬁc precipitation levels within the range considered in the region to lead a shift towards deciduous species dominated woodlands (around 600 mm, variable with mean temperature). Only trees at warmer sites showed symptoms of growth decline, most likely explained by water stress increase in the last decades affecting the highly transformed open (i.e. low competition) tree structure. Stands at colder locations did not show any negative growth trend and may beneﬁt from the current increase in winter temperatures. Coinciding with the decrease in productivity, trees at warmer sites responded more to moisture availability, exhibited a slower response to precipitation and reached maximum growth at higher precipitation levels than trees at colder sites. This suggests that warmer stands are threatened by climate change. The non-linear response of growth to precipitation described is meaningful for different ecological applications and provides new insights in the way trees respond to climate.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: competition; Dendroecology; Drought; Non-linear response; water stress

Effects of a severe drought on Quercus ilex radial growth and xylem anatomy - Gil-Pelegrín, Eustaquio; Corcuera, Leyre; Camarero, Jesús Julio (Trees - Structure and Function, 2004)
We assessed the response of Quercus ilex subsp. ballota to the severe summer drought recorded in 1994 in NE Spain through the study of changes in radial growth and wood anatomy. We selected a coppice stand in the Iberian Peninsula, which is characterized by a Mediterranean climate under continental influence. We measured internode length, tree-ring width, mean and maximum vessel diameter, and vessel density for 1981– 1997. The annual predicted hydraulic conductance (Kh) was calculated following Hagen-Poisseuille’s law. We compared the tree-ring width, vessel diameter and Kh of Q. ilex subsp. ballota and co-existing ring-porous oaks (Q. faginea, Q. pyrenaica) for a dry summer (1994) and a wet summer (1997). To evaluate the drought-resistance of xylem for Q. ilex subsp. ballota (dominant under continental conditions) and Q. ilex subsp. ilex (dominant in mild areas) we determined vulnerability curves. Dimensionless indices of internode length, tree-ring width, and vessel density were compared with climatic data (monthly total precipitation and mean temperature) using correlation analyses. Internode length, tree-ring width, Kh, and mean and maximum vessel diameter declined in 1994. According to vulnerability curves, Q. ilex subsp. ballota showed a greater drought resistance than Q. ilex subsp. ilex. During the year of growth, we found a positive influence of January and June–August precipitation on the internode length, tree-ring width, and vessel density. The response of Q. ilex subsp. ballota radial-growth to summer drought was comparable to that of Q. faginea latewood. Overall, growth and wood anatomy of Q. ilex subsp. ballota showed a plastic response to drought.
Keywords: cavitation; climate; Dendroecology; vulnerability curve; Xylem

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L; Tognetti, Roberto; Bräker, Otto U; Schoch, Werner; Innes, John L (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L.; Tognetti, Roberto; Bräker, Otto U.; Schoch, Werner; INNES, JOHN L. (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
The following values have no corresponding Zotero field: accession-num: 12620063
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Comparative stem-growth rates of Mediterranean trees under background and naturally enhanced ambient CO2 concentrations - Tognetti, Roberto; Cherubini, Paolo; INNES, JOHN L. (New Phytologist, 2000)
Ring widths of five Mediterranean forest tree species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Quercus ilex and Quercus pubescens) growing close to a natural source of CO2 in Tuscany, Italy and at a nearby control site were compared. At the CO2-enriched site, trees have been growing for decades under elevated CO2 concentrations. They originated from parent trees that also grew under elevated CO2 in natural conditions, and they have been continuously exposed to elevated CO2 throughout their growth. Tree-ring series from each of the species were prepared. Assigning calendar dates to rings was difficult but possible, and ring-width series were built for all species. The ring-width data were analysed using a two-sided t-test to assess if there was a difference between the radial growth at the CO2-enriched site and the control site. The cumulative basal area at the same cambial age at both sites was also compared using a Wilcoxon test. Radial growth of trees at the CO2-enriched site was not significantly different from growth at the control site. For each species, year by year, radial growth at the CO2-enriched site was tested against the control site and significant differences were found in only a few years; these differences were not synchronous with extreme climatic events. The expected increase in above-ground productivity, as one of the ecosystem responses to increasing CO2 during drought stress, was not observed in this Mediterranean woody plant community, despite being water-limited. Other resource limitations, such as low nutrient availability (common in the Mediterranean region), may have counteracted the positive effect of elevated CO2 under drought stress, or trees may have acclimated to the high CO2.
The following values have no corresponding Zotero field: publisher: Cambridge University Press
Keywords: Arbutus unedo (strawberry tree); Carbon Sequestration; Dendroecology; Mediterranean trees; natural CO2 springs; Quercus ilex (holm oak); tree rings; water stress

Comparative stem-growth rates of Mediterranean trees under background and naturally enhanced ambient CO2 concentrations - Tognetti, Roberto; Cherubini, Paolo; Innes, John L (New Phytologist, 2000)
Ring widths of five Mediterranean forest tree species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Quercus ilex and Quercus pubescens) growing close to a natural source of CO2 in Tuscany, Italy and at a nearby control site were compared. At the CO2-enriched site, trees have been growing for decades under elevated CO2 concentrations. They originated from parent trees that also grew under elevated CO2 in natural conditions, and they have been continuously exposed to elevated CO2 throughout their growth. Tree-ring series from each of the species were prepared. Assigning calendar dates to rings was difficult but possible, and ring-width series were built for all species. The ring-width data were analysed using a two-sided t-test to assess if there was a difference between the radial growth at the CO2-enriched site and the control site. The cumulative basal area at the same cambial age at both sites was also compared using a Wilcoxon test. Radial growth of trees at the CO2-enriched site was not significantly different from growth at the control site. For each species, year by year, radial growth at the CO2-enriched site was tested against the control site and significant differences were found in only a few years; these differences were not synchronous with extreme climatic events. The expected increase in above-ground productivity, as one of the ecosystem responses to increasing CO2 during drought stress, was not observed in this Mediterranean woody plant community, despite being water-limited. Other resource limitations, such as low nutrient availability (common in the Mediterranean region), may have counteracted the positive effect of elevated CO2 under drought stress, or trees may have acclimated to the high CO2.
Keywords: Arbutus unedo (strawberry tree); Carbon Sequestration; Dendroecology; Mediterranean trees; natural CO2 springs; Quercus ilex (holm oak); tree rings; water stress